Active audiences and journalism. Analysis of the quality and regulation of the user generated contents - Meso Ayerdi, Koldobika (ed.) (Universidad del País Vasco, 2016)
Even if journalism has always been in continuous transition, nowadays it seems to be going through a time of especial uncertainty and changes, similar to that experienced when the Web and online media emerged. Together with constant updating, abundance of information and innovation in the formats, genres and devices for consumption, nowadays participatory journalism represents one of the main challenges of journalism and the mass media. The Web's evolution from 1.0 to 2.0 has given rise to a more complex scenario, which is marked by greater audience presence in the communicative process. This citizens' direct participation in news production has even led to the replacement of the traditional mainstream media as primary sources of information. Among other consequences, it has been necessary to recycle journalists' skills in Web 2.0 communication activity. Since audiences, citizens-users or clients -according to the case- are more and more involved, active and social, it has been also crucial to develop expert professional profiles. That is, those changes have introduced new patterns of communication and increased new forms of creative expression, journalism and participation. This book approaches this adaptation by analyzing different experiences and models of citizen participation and interactive journalists, besides paying special attention to the debate on the quality of user-generated content and the value of the relation between the media and audiences to strengthen the traditional democratizing value of mediated communication.